UTILIZING MOBILE-ASSISTED LANGUAGE LEARNING (MALL) TO ALLEVIATE SPEAKING ANXIETY AMONG EFL STUDENTS - Putri, Nanda Allya; Degeng, Putu Dian Danayanti (University of Kuningan, 2024)
This study employs a sequential explanatory mixed-methods case study approach to examine the effectiveness of Mobile-Assisted Language Learning (MALL) applications in reducing speaking anxiety among English as a Foreign Language (EFL) learners. The research targeted 17 twelfth-grade science students, comprising ten males and seven females aged 17 to 19, using a combination of web-based surveys and semi-structured interviews for data collection. The findings underscore significant positive outcomes, highlighting the substantial role of MALL applications in enhancing students’ proficiency in English. Notably, an analysis of responses to survey item number 22 shows that 64.7% of students agree that MALL applications have been instrumental in alleviating their speaking anxiety. This study provides valuable contributions to the field of language education by presenting evidence-based practices that leverage MALL applications to lower speaking anxiety and boost EFL learners’ speaking skills, proposing innovative and effective approaches for language learning.